No rastro do marfim : a circulação do marfim in natura entre Luanda, Benguela, Brasil e Lisboa (1723-1808) - Rogéria Cristina Alves (2021)
The research's main objective is to elucidate the Atlantic circulation of elephant ivory, exported from the ports of Luanda and Benguela, between the years 1723 and 1808. To this end, it follows the paths taken by this raw material, whose circulation was parallel to the slave trade. Based on historical sources of Portuguese origin, this research is dedicated to the ivory trade in natura that took place under the administrative rules of the royal contracts and the royal monopoly. Thus, we investigate the official export of this ivory, we follow it from the operation of the contracts in Africa until its final destination, emphasizing the operational, administrative and social aspects of this movement. Therefore, we approach the transformation of the ivory in natura to manufactured objects, investigating especially the productions of the Real Fábrica de Pentes de Marfim, Caixas de Papelão e Vernizes, installed in Lisbon in 1764 and whose production were directly related to the ivory coming from the ports of Luanda and Benguela. Our central argument is that the role of this ivory in natura as a commodity was important for Portuguese finances, still in the 18th century and its history was underestimated by historiography. Based on the theory of Atlantic History, this research is based on an extensive analysis of documentary sources located in three different continents, which provide information on the circulation and commercialization of ivory from West-Central Africa, through Brazil and reaching Lisbon.